PENGARUH PRODUCT KNOWLEDGE, PERCEIVED QUALITY, PERCEIVED RISK, DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION PADA MOTOR KAWASAKI NINJA 250 FI DI KOTA SEMARANG - Adi Kurniawan, Henricus; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2018)
This study aims to examine the factors affecting purchase intention. These factors are namely product knowledge, perceived quality, perceived risk, perceived value.The population in this study were all people who knew but had never bought a Kawasaki Ninja 250 Fi motorcycle product, who lived in Semarang City. The sample was selected using purposive sampling method. Based on the criteria that have been determined, obtained a sample of 100 respondents.The data analysis technique used in this study is multiple linear regression. The results showed that product knowledge and perceived value had a positive and significant effect on purchase intention. Meanwhile perceived quality and perceived risk are not significant to purchase intention.